Urban Water Management in Malaysia: A Review of Legislative Framework - Salleh, Dani; Said, Mohd Syahril; Junaidi, Noni Harianti; Ahmad, Za’im (UUM Press, 2023)
The presence of urban rivers poses significant challenges for local authorities in their efforts to create sustainable and habitable urban river environments. This situation has led to various repercussions for the health of urban river ecosystems. To mitigate these issues, it is imperative that development projects’ environmental impacts are effectively managed by the relevant authorities, ensuring the sustainability of urban development and urbanization. It is worth emphasizing that in environmentally sensitive areas, particularly when planning large projects, the consideration of environmental factors should be a top priority. As such, this discussion will focus on how local planning authorities in the country devise strategies to address the challenges associated with urban river development projects.